(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the surgical outcome of testicular injury in Viet Duc Hospital from January 2017 to June 2022. Subjects and methods: The study was conducted as a retrospective cohort, by convenient sampling of 38 patients who were treated for testicular injury at the Center for Andrology and Sexual Medicine, Viet Duc Hospital from January 2017 to June 2022. Results: The mean age was 27,84 ± 10,71 years (10-53 years) and 63,2% patients got married. The most common cause was traffic accident (52,6%). The mean day of hospitalization was 15,26 ± 17,14 days (6-32 days). There are 22 patients (57,8%) had right testicle injury and one patient had both testicle injury. The time of surgery was 65,44 ±25,15 minutes (45-100 minutes). 34 patients were treated with conservative surgery and 4 patients were orchiectomy. No patient had bleeding or necrotic testicular and 2 patients had infection wound in postoperative. The median follow-up was 30 months (2–57 months). 19/38 patients had reduced the volume of testicle, 7/25 patients reduced the testosterone level, 9/16 patients had the abnormal semen analysis. None had chronic testicular pain. Conclusion: Testicular injury is a urological emergency mainly happened in young people, early diagnosis and proper medical interventions would increase the possibility of testis salvage and protecting testicular functions.